Práticas informacionais: LGBTQI+ e empoderamento no espaço LGBT - Silva, Laelson Felipe da (2019)
Human rights violations of lesbian, gay, bisexual, transvestite, transsexual, queer and intersex (LGBTQI +) express themselves daily in different forms and types of prejudices, discrimination and violence, ranging from psychological, physical, sexual violence, threats, until death. The challenge is not coping with the violence and homicide of LGBTQI +. Another hypothesis is located in the construction of a socio-historical of heteronormative character, which censures as transgressions of the heterosexual norm. What has led us to question ourselves as a society marked by heterogeneity between informational people and the process of empowerment of transgender individuals? What is the use as you are in analysis as being informational of the users center LGBT Rights Reference Center and the Confrontation in Homophobia in Paraíba and as its influences in the process of empowerment. It uses the theoretical contributions: gender relations, informational practices, empowerment and habitus. A research is characterized as descriptive and correlational. It has documental and field characteristics. It has quantitative and qualitative nature. It made the use of records of attendance of people 544 users as attended in LGBT in the period between 2015 and 2017. Descriptive statistics was used as an instrument of analysis of numerical data. In the second moment, to understand how the information is informative and search the meanings that the transsexual subjects have to their experiences and their expressions of expression applying the semi - released interviews. The sample comprised a transvestite, a transsexual woman and four trans men. Thus, we use a qualitative approach and through content analysis as the subcategories and their subcategories: meanings of the transsexual experience (subcategories: Perception of self, appointment, family, school, work); informational techniques of transsexuals in the interaction with the Espaço LGBT (subcategories: sources of information, knowledge of the Espaço LGBT, services used); The information and empowerment (subcategories: resignification, emancipatory actions, information in the process of empowerment, importance of the informative information of the Espaço LGBT). An analysis of the results obtained in this study could have been carried out through an access information system and / or disseminated by the Espaço LGBT with the process of empowerment of transsexual individuals. This method, the process public in the practice information has not supported, there are, the, which is not, which is not, the identities of genitive distanced the legitimized by the heterosexual norm are conceived as abject and marginalized. Thus, access to the database enabled entrepreneurial companies to carry out individual and collective emancipatory actions that consolidate the continuity of the empowerment process. Finally, it is reiterated that Information Science is configured as a field of fundamental knowledge in the subversion of inequalities and a generation of knowledge about the hegemonic ones oriented towards the sexual and gender differences.